What is justice for survivors of Gujarat 2002? - George, Sheba; Kannabiran, Kalpana (2007)
The United Nations Committee on the Elimination of Discrimination against Women recently pulled up the government of India for an inadequate response on the 2002 Gujarat riots despite specific queries by the committee on the issue. The concluding comments of the CEDAW offer a significant advocacy tool for human rights organisations working to secure justice for the riot victims. - Reproduced.
Keywords: Riots - India - Gujarat; Riots